Screening plant growth effects of sheep slaughterhouse waste-derived soil amendments in greenhouse trials - Yetilmezsoy, Kaan; Kiyan, Emel; Ilhan, Fatih; Ozcimen, Didem; Kocer, Anil Tevfik (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2022)
Ameliorative effects of sheep slaughterhouse waste-derived soil amendments (struvite, blood meal, bone meal) were explored and quantified by a series of comparative greenhouse trials. A scoring matrix system was developed for 25 different test plants using 300 agricultural measurements obtained for three basic growth parameters (fresh-dry plant weights and plant heights) and four different fertilizer sources including solid vermicompost. More than 70% of NH4+-N recovery from sheep slaughterhouse wastewater was achieved using a chemical combination of MgCl2 center dot 6H(2)O + NaH2PO4 center dot 2H(2)O, a molar ratio of Mg2+:NH4+-N:PO43-P = 1.2:1:1, a reaction pH of 9.0, an initial NH4+-N concentration of 240 mg/L, and a reaction time of 15 min. According to SEM micrographs, surface morphology of struvite exhibited a highly porous structure composed of irregularly shaped crystals of various sizes (11.34-79.38 mu m). FTIR spectroscopy verified the active functional groups on the proximity of all fertilizer sources within the spectral range of 500-3900 cm(-1). TGA-DTG-DSC thermograms of struvite revealed that the mass loss occurred in two temperature regions and reached a maximum mass loss rate of 1.63%/min at 317 degrees C. The average percentages of increase (57.55-100.62%) and performance points (69-79) corroborated that the fertility value of struvite ranked first on average in cultivation of the analyzed plant species. Findings of this agro-valorization study confirmed that sheep slaughterhouse waste-derived fertilizers could be a beneficial way to promote bio-waste management and environmentally friendly agriculture.
Keywords: Ammonium recovery; Greenhouse study; Plant growth; Sheep slaughterhouse; Soil amendment; Struvite precipitation; WATER; RECOVERY; MANAGEMENT; NITROGEN; YIELD; PH; Environmental Sciences & Ecology